A relational view of start-up firms inside an incubator: the case of the ARCA consortium. Issue 4 (3rd April 2018) - Di Fatta, Davide; Caputo, Francesco; Dominici, Gandolfo
Abstract : Purpose: Analyzing the entrepreneurial ecosystem related to the ARCA consortium, the purpose of this paper is to study the relationships among the start-up firms inside an incubator. Design/methodology/approach: Thanks to the adoption of the relationships concentric model and the density concentric model, the paper highlights the role of relational conditions for innovative projects in partnership among the incubated firms. Reflections herein are tested via a qualitative research approach based on a single case study: the ARCA consortium. Findings: This research found that about 32 percent of relationships inside the incubator support the emergence of short-term relationships among the incubated firms. Furthermore, about 18 percent of the relationships support the emergence of strong collaborative strategies for the implementation of long-term relationships resulting in innovative pathways: innovative projects in partnership. Originality/value: The most interconnected firms inside the incubator are those that play a central role also in the innovation pathway developing the higher number of innovative project in partnership. This finding emphasizes a correlation between collaborative relationships and innovation inside an incubator ecosystem.